CHARACTERISTICS OF INTEGRATED TEACHING IN PRIMARY SCHOOLS - Abdinazar SALOMOV (Scholar Express Journal, 2023)
In this article discussed that, importance of interdisciplinary integration, some of the requirements and conditions for the introduction of integrated education in the primary grades, and described in detail the general features of the integrated course.
Keywords: placements; enterprises; integration; interdisciplinary integration